Protótipo de móvel incorporando laminados e compensados curvos com madeiras da Amazônia - Pinto, Paulo Silva; Pennington, David Rodney Leonel; Nascimento, Claudete Catanhede Do; Cunha Neto, Zulmar Bonates da; Suano, José Murilo Ferraz (Acta Amazonica, 1989)
In the study of some hardwood species as alternative use in furritive design, two species were selected based on its own caracteristics such as> decorative design, prototype Lightness, resistance under use conditions, etc. The selected species were: Guariúba [Clarisia racemoma) e Cedrorana (Cedrelinga catenaeformis). From each one species, prototype, chains was assembled by laminated wood and Plywood.